2012
DOI: 10.4103/0300-1652.103545
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of 2D ultrasound prenatal sex determination

Abstract: Background:Pregnant women have been curious about the sex of their unborn child. The advent of ultrasound, its application into medicine, and the revolutionary changes in its resolution and function has led to the ability to assign a sex to these unborn children, thereby allaying the anxiety of these women but with consequent emergent ethical, moral, psycho-social, and medico-legal issues. The objectives were to determine the accuracy of sonographic prenatal sex determination, perform binary classification tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…A recent study showed that women are relieved when fetal gender is disclosed to them and a great majority of them remain happy even when the gender is not the desired type. [ 21 ] However on the other hand, the anxiety may be indicative of real danger for the woman as failure to have a male child could propel the husband to marry additional wife/wives. This desperation is because of societal pressure to perpetuate one's lineage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that women are relieved when fetal gender is disclosed to them and a great majority of them remain happy even when the gender is not the desired type. [ 21 ] However on the other hand, the anxiety may be indicative of real danger for the woman as failure to have a male child could propel the husband to marry additional wife/wives. This desperation is because of societal pressure to perpetuate one's lineage.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Benin City, Nigeria, the women were happy even when the desired gender was not found. [ 21 ] These diametrically opposed findings could be as a result of differences in the value system of the Igbos and people in Edo area. Loss of interest in a pregnancy as a result of undesired fetal gender may consequently lead to induced criminal abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound in combination with abortion is a prenatal rather than a preimplantation technique for sex selection and is thus more invasive and associated with considerable medical risk. The sex of the fetus can be detected with ultrasound at week 11, at the earliest, which means that abortions may have medical risks, especially in low-income countries (Igbinedion & Akhigbe, 2012). 3 While this remains the most prevalent technique for sex selection in low-and middle-income countries (mostly used to select male children), it is rarely used in high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal determination of fetal sex traditionally relies on ultrasound scan visualization of well-defined external genitalia anatomical features in second and third trimesters. More recently, however, other ultrasound markers such as the direction of the genital tubercle, anogenital distance, sagittal sign, and fetal heart rate (FHR) differences between sexes in the first trimester have been evaluated as reliable predictors of fetal gender [1,2]. This rising desire for first-trimester sex determination among women is believed to be due Sudan Journal of Medical Sciences Olufemi Adebari Oloyede and Mustafa Adelaja Lamina to mothers' desire for early planning of social aspects of pre-birthing activities.…”
Section: Introductionmentioning
confidence: 99%